Kebutuhan Mendesak Untuk Menegakkan Kembali Pendidikan di Indonesia - Raka, Ida I D. Gede (Faculty of Psychology, Universitas Surabaya, 2007)
The causal factor leading to Indonesia’s failure in economic and social development is assumed to be the national education system. Education is deemed as not able to maintain balance and harmony between the brain and mind education aspects. This gap is clearly seen in various life dimensions. The weaknesses of the education system—already implemented for more than 30 years—are of course impossible to be settled quickly and easily. The enhancement of teacher’s quality, change of the evaluation method, awakening of national awareness of the importance of education are proposed as a comprehensive and systemic solution. Kekurangberhasilan bangsa Indonesia dalam pembangunan ekonomi dan sosial budaya dipandang berawal dari kelemahan sistem pendidikan nasional. Pendidikan dianggap kurang mampu menjaga keseimbangan dan keselarasan aspek pendidikan “otak” dan “hati”. Kesenjangan ini dapat terlihat dengan mudah dalam berbagai segi kehidupan. Kelemahan sistem pendidikan yang telah berlangsung selama lebih dari tiga dekade ini tentu saja tidak dapat diselesaikan dengan cepat dan mudah. Perbaikan kualitas guru, perubahan metode evaluasi, dan penggugahan kesadaran nasional tentang pentingnya pendidikan ditawarkan sebagai usulan solusi yang komprehensif dan sistemik.